Overexpression of HER-2 in MDA-MB-435/LCC6 Tumours is Associated with Higher Metabolic Activity and Lower Energy Stress - Dragowska, Wieslawa H. (Sci Rep, 2016)
Overexpresssion of HER-2 in the MDA-MB-435/LCC6 (LCC6(HER-2)) tumour model is associated with significantly increased hypoxia and reduced necrosis compared to isogenic control tumours (LCC6(Vector)); this difference was not related to tumour size or changes in vascular architecture. To further evaluate factors responsible for HER-2-associated changes in the tumour microenvironment, small animal magnetic resonance imaging (MRI) and positron emission tomography (PET) were used to measure tumour tissue perfusion and metabolism, respectively. The imaging data was further corroborated by analysis of molecular markers pertaining to energy homeostasis, and measurements of hypoxia and glucose consumption. The results showed a strong trend towards higher perfusion rates (~58% greater, p = 0.14), and significantly higher glucose uptake in LCC6(HER-2) (~2-fold greater; p = 0.025), relative to control tumours. The expression of proteins related to energy stress (P-AMPK, P-ACC) and glucose transporters (GLUT1) were lower in LCC6(HER-2) tumours (~2- and ~4-fold, respectively). The in vitro analysis showed that LCC6(HER-2) cells become more hypoxic in 1% oxygen and utilise significantly more glucose in normoxia compared to LCC6(Vector)cells (p < 0.005). Amalgamation of all the data points suggests a novel metabolic adaptation driven by HER-2 overexpression where higher oxygen and glucose metabolic rates produce rich energy supply but also a more hypoxic tumour mass.